ANALISIS POTENSI PEMBENTUKAN POS UKK PADA GAPOKTAN NGUDI LUHUR GIRIWOYO - Tinuk Setyo Rini; Anik Setyo Wahyuningsih (Jurnal Kesehatan Masyarakat, 2022)
The informal economy sector which is dominated by agriculture covers 56.50 percent (74.04 million people) of the main occupations of Indonesian population. The informal economy sector provides support for economic growth by absorbing the existing workforce. On the other hand, jobs in the informal economy are often in a precarious condition. To deal with these problems, the government established the Occupational Health Post program. The type of this research is qualitative – case study. Data were collected by conducting in-depth interview, direct observation, and documentation studies. The data obtained is then analyzed by qualitative analysis and used to describe a SWOT analysis of the potential of the Occupational Health Post establishment in the farmer group. The result shows that there is a potential for the establishment of the Occupational Health Post in Gapoktan Ngudi Luhur as well as various strategic options that can be applied to establish the Occupational Health Post.